Răspunsuri

2014-08-26T14:49:27+03:00
X+y=5 / ()^2
x^2+2xy+y^2=25

x^2-y^2=45=> x^2=45+y^2

Inlocuim in prima ecuatie:

45+y^2+2xy+y^2=25
2y^2+2xy=25-45
2y^2+2xy=-20
2y(y+x)=-20   dar in problema ne zice ca x+y=5, deci inlocuim
2y*5=-20
10y=-20
y=-2

x+(-2)=5
x-2=5
x=5+2
x=7

5y-5x=
5(y-x)=
5*(-2-7)=
5*(-9)=-45  sau se putea face fara a scoate factor comun

5*(-2)-5*7=
-10-35=-45
1 5 1
  • Utilizator Brainly
2014-08-26T14:58:47+03:00
A+b=15

a²-b²=45 =>
(a+b)*(a-b)=45 =>
15*(a-b)=45
a-b=3

5a-5b=5*(a-b)=5*3=15